Fundamentals of polarimetric remote sensing - Schott, John R., 1951- (Tutorial texts in optical engineering ;, 2009)
This text is for those who need an introduction to polarimetric signals to begin working in the field of polarimetric remote sensing, particularly where the contrast between manmade objects and natural backgrounds are the subjects of interest. The book ta